Transport of direct current electricity: research and prospects - Dzhumamukhambetov, Nasikhan; Yashkov, Vladimir; Kulzhanov, Dyussembek; Konarbayeva, Akmaral; Arstanaliyev, Essengeldi (Institute of Advanced Engineering and Science, 2025)
The purpose of this study is to analyse the technical, economic, and environmental aspects of direct current electricity transport and to assess its potential in accordance with modern requirements for sustainable energy and infrastructure. The methods used include analytical method, classification, functional method, statistical method, synthesis. The study revealed that the use of direct current has the potential to increase the capacity of power transmission lines, which is especially important in a dynamically developing industrial sector. It should be noted that direct current networks have no phase shifts and no notions of static and dynamic stability, making them ideal for long-distance power transmission. As a result of the conducted research, it can be concluded that the use of direct current in technologies can increase the efficiency and reliability of energy systems, especially with an increase in consumption and load on the grid. Direct current power transmission technologies meet the requirements of sustainable energy supply, providing economic efficiency and reducing environmental impact.